Biochar as Improver of Methane Production in Anaerobic Digestion of Food Waste - Florio, Ciro; Giudicianni, Paola; Pirozzi, Domenico; Pasquale, Vincenzo; Ragucci, Raffaele; Dumontet, Stefano (Journal of Environmental Accounting and Management, 2026)
Anaerobic digestion of food waste is aimed both at the reduction of the volume of waste and the production of methane. Carbonaceous additives such as activated carbons were widely studied as enhancer of methane production. In this paper a low-cost alternative additive, the biochar, was proposed to assess its use for improving both the operational stability and the energetic output of anaerobic digestion. The main objective of the present work is to assess and quantify the increase of CH4 yields induced by the biochar addition and to identify all the main mechanisms responsible of this improvement. The risk related to the Polycyclic Aromatic Hydrocarbons release from biochar in the anaerobic digestion media was discussed as well. To this aim, biochar obtained from steam assisted slow pyrolysis of Populus nigra L. up to 600 °C was used. Anaerobic digestion of food waste mixture was carried out in a batch reactor in mesophilic conditions (37 °C). Four tests were conducted by adding 0, 1, 4 and 10 wt% of biochar on wet food waste mixture basis. Results showed that more CH4 is produced even in the first hours of the anaerobic digestion test when 10 wt% of biochar was added to the food waste mixture (about 65 wt% more at 96 h), thus denoting a reduction of the lag phase. A total increase of CH4 yield of 14 and 42% when 4 and 10 wt% of biochar was added to the food waste mixture. In conclusion, analyses of both the liquid phase during the tests and biochar sampled at the end of anaerobic digestion process revealed that biochar favored the decomposition of acetic acid, adsorbed some inhibitors such as butyric acid, and provided a suitable habitat for microbial colonization.